Synthesis and Cycloaddition Reactions of Stabilized Münchnones. Issue 16 (20th May 2016) - Kakaawla, Taban K. K.; Hartley, Will C.; Harrity, Joseph P. A.
Abstract : A family of stabilized münchnones bearing an acyl group at C4 have been prepared and studied in alkyne cycloaddition reactions. These reactions are highly regioselective, and the method represents a rapid and straightforward route to densely substituted pyrroles. Finally, the C4‐stabilizing units can be further manipulated to furnish carboxylic acid and amide groups, or removed altogether to provide unsubstituted pyrroles. Abstract : Stable and selective: Stabilized münchnones bearing an acyl group at C4 undergo highly regioselective alkyne cycloaddition reactions. This method represents a rapid and straightforward route to densely substituted pyrroles, whereby the stabilizing group is amenable to further derivatization.